Gift Box By Qiessy / Balqis Najiha Yusri - Yusri, Balqis Najiha (2021)
From this report, Gift Box by Qiessy is an online shop that sells two types of gift box and divided into two which is Gift Box for Students and Gift Box for Her. Gift Box by Qiessy is dedicated to serve our loyal customers and offer the best we can to give what customers need. My online shop is managed by three people, I am the owner and my two sisters are the manager. Our customer service is trained to always serve customers politely and with a full of hearts because, from our service, customers be able to know if they are treated well or not. If they feel, they are not being treated well, they might consider finding other gift box shop that provides more excellent customer service. Also, our customer segment mostly for woman and girls whereby girls which are a student or even though she is not student she can buy Gift Box for Students, as the gift box serves joy and happiness to their recipient. Moreover, for Gift Box for Her, it is a complete gift that will sparks a bundle of excitement to them as it has a lot of makeup and skincare for them to try out. This gift box will indulge and spoil them in their free time when they are back from their work. The price is affordable and made with high-quality products and we also provide them with free postage for all around Malaysia and free COD available to KL and Selangor to attract customers to buy our gift box. As a result, in Malaysia, whereby we need to stay at home and cannot go outside if there are no important matters. By doing these services, peoples can stay at home and let us get things done and deliver until in front of their house. Since, right now, many people do not know what type of gift box is suitable to give to their loved ones, by choosing our gift box, they just can relax as our gift box is the right choice. In addition, many gifts box shop is anywhere and can reach out easily, no matter where they conduct their shop, such as ecommerce, social media or via communication social media such as Whatsapp. What makes Gift Box by Qiessy is differ from others is that on how we serve our customers, we value them and only provide the legit and authentic gift boxes, so by that, the customers will feel our honesty and our full commitment to them. On the other hand, Gift Box by Qiessy might consider releasing another type of gift box instead of the two-gift box mentioned above because we want to achieve more target segments and makes our gift shop familiar and well recognized by others. Lastly, Gift Box by Qiessy will strive further to be the best and hoping that customer will always remember to choose our products first instead of other in the future.